Comprehensive Analysis of Detection Methods for Over-the-counter Codeine: A Systematic Review - Anagha Ravindran; Tina Sharma; Mahipal Singh Sankhla (Journal of Forensic Science and Medicine)
Concerns have been raised about how readily available over-the-counter (OTC) codeine formulations may be contributing to the expanding opioid epidemic. Focusing on the analytical methods used to find and measure codeine in various sample types, this systematic review provides a thorough analysis of OTC codeine abuse and misuse. It also includes case studies that highlight the seriousness of the problem by describing codeine-related deaths and intoxications. A wider view of the issue is provided by the crime statistics in this paper that relate to codeine and related drugs in India from 2017 to 2021. A thorough electronic search covering the years 2012–2022 was carried out from February 2023 to April 2023 to compile this review. Google Scholar, Science Direct, and PubMed were just a few of the search engines used. While crime statistics for India were sourced from the National Crime Records Bureau website, case reports were gathered from the Journal of Medical Case Reports and Wiley Online Library. Studies examining OTC codeine, its abuse, and the analytical methods used for its detection and quantification were all covered by our inclusion criteria. Case reports involving codeine seizures, fatalities, and intoxications were also included, along with review and research papers. On the other hand, studies with little connection to OTC codeine, books, documents, clinical trials, meta-analyses, non-English papers, and publications with only abstracts were disregarded. With the help of this systematic review, we located 531 studies in databases, 83 of which satisfied our inclusion requirements. Our research is organized into sections that cover crime data, case studies of codeine-related overdoses or deaths, and detection methods. For researchers, medical professionals, and policymakers actively engaged in the fight against codeine abuse and the societal harms it causes, this review is an invaluable resource.